2019
DOI: 10.11604/pamj.2019.32.103.15743
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility patterns of Staphylococcus aureus strains isolated at the Yaounde Central Hospital, Cameroon: a retro prospective study

Abstract: Introduction Staphylococcus aureus is an important pathogen responsible for hospital and community acquired infection(s). Emerging resistance to methicillin in this organism has left physicians with few therapeutic alternatives to treat infections caused by it. This study was aimed at determining the antibiotic susceptibility patterns of Staphylococcus aureus strains isolated at the Yaounde Central Hospital, Cameroon. Methods fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Antimicrobial susceptibility testing showed high resistance to penicillin, cotrimoxazole, tetracycline, ofloxacine and gentamicine. A similar report from Nepal also showed inefficacy of these antibiotics for treatment of local isolates [54]. Meanwhile rifampicin, fusidic acid, lincomycin and minocycline showed efficacy against our isolates.…”
Section: Plos Onesupporting
confidence: 75%
“…Antimicrobial susceptibility testing showed high resistance to penicillin, cotrimoxazole, tetracycline, ofloxacine and gentamicine. A similar report from Nepal also showed inefficacy of these antibiotics for treatment of local isolates [54]. Meanwhile rifampicin, fusidic acid, lincomycin and minocycline showed efficacy against our isolates.…”
Section: Plos Onesupporting
confidence: 75%
“…Others authors obtained same range, Garoy in Eritrea [36] and Ebob in Douala [20]. [41]. However, rifampicin, fusidic acid, lincomycin, minocyclin showed high rate of sensitivity, many authors also obtained the same results.…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 78%
“…Several studies have shown foods of animal origin to be an important reservoir of S. aureus [24][25][26][27][28], and there are increasing reports on foodborne disease outbreaks linked to S. aureus. In Cameroon, most reports on S. aureus are mainly from clinical samples and hospital environment [29][30][31][32]. Data on this pathogen as a food safety concern in Cameroon are therefore insufficient.…”
Section: Introductionmentioning
confidence: 99%